New fractional cosine transform and its application - ZHANG Yong-liang; ZENG Yi-cheng (Tongxin xuebao)
A new Fractional Cosine Transform was proposed. It was a weighted combination of the first two integer-order cosine transforms of the original signal, and it has the same eigenvectors as the cosine transform’s, but the different eigenvalues which have a periodicity of two. When the periodicity from two to K was extended, K period fractional cosine transform was obtained. Two algorithms were deduced and the advantages of the new fractional cosine transform were analyzed. At last, the application in digital watermark of aural signals was discussed.